Evaluating disparities in delivery of neoadjuvant guideline‐based chemoradiation for rectal cancer: A multicenter, propensity score‐weighted cohort study. Issue 5 (23rd June 2021) - Lau, Lung W.; Kethman, William C.; Bingmer, Katherine E.; Ofshteyn, Asya; Steinhagen, Emily; Charles, Ronald; Dietz, David; Stein, Sharon L.
Abstract: Background: Despite guideline recommendations, some patients still receive care inappropriate for their clinical stage of disease. Identification of factors that contribute to variation in guideline base care may help eradicate disparities in the treatment of early and locally advanced rectal cancer. Methods: The American College of Surgeons National Cancer Database from 2010 to 2015 was analyzed with propensity score weighting to identify factors associated with delivery and omission of neoadjuvant guideline‐based chemoradiation (GBC) for those with early and locally advanced rectal cancer. Results: Only 74% of patients with rectal cancer received stage‐appropriate neoadjuvant chemoradiation; 4544 (88%) of those with early stage disease and 8675 (68%) in locally advanced disease. Chemotherapy and radiotherapy were not planned in 27% and 34% respectively, of those who did not receive GBC. Factors associated with receipt of non‐guideline‐based neoadjuvant chemoradiation were age >65 years, Medicare insurance, treatment at a community facility, West‐South‐Central geography, having locally advanced disease, and Charlson–Deyo score >3. Receipt of ideal guideline‐based neoadjuvant chemoradiation conferred a survival benefit at 5 years. Conclusion: Patient and non‐patient factors contribute to disparities in guideline‐based delivery of neoadjuvant chemoradiation in the treatment of rectal cancer. Identification of these risk factors are important to help standardize care and improve survival outcomes Highlights: Despite guideline recommendations, many patients do not receive stage appropriate neoadjuvant chemoradiation. This study using NCDB database show that receipt of guideline based care (GBC) is associated with improved 90 day mortality in all groups and 5 year overall survival in those with locally advanced disease. Factors for affecting delivery of GBC include Charlson‐Deyo score, age, Medicare insurance, geography, locally advanced disease, and treatment facility type.